Clinically relevant profiles of myelin content changes in patients with multiple sclerosis: A multimodal and multicompartment imaging study. (October 2022) - Lazzarotto, Andrea; Tonietto, Matteo; Poirion, Emilie; Battaglini, Marco; Palladino, Raffaele; Benoit, Charline; Ricigliano, Vito AG; Maillart, Elisabeth; De Stefano, Nicola; Stankoff, Bruno; Bodini, Benedetta
Objective: To investigate the clinical relevance of individual profiles of cortical and white matter lesion myelin content changes combining magnetisation transfer imaging (MTI) and 11C-PiB-positron emission tomography (PET) in patients with multiple sclerosis (MS). Methods: MTI and [ 11 C]PiB-PET acquired in 19 patients with MS followed up over 2–4 months and in seven healthy controls (HCs), were employed to generate individual maps of cortical and white matter (WM) lesion myelin content changes, respectively. These maps were used to calculate individual indices of demyelination and remyelination, and to investigate their association with clinical scores. Results: Cortical remyelination ranged between 1% and 5% of the total cortical volume (17%–45% of the cortical volume demyelinated at baseline). WM lesion remyelination ranged between 8% and 22% of the lesional volume. An extensive cortical remyelination was associated with a shorter disease duration (rho = −0.63, p = 0.01) and, in combination with WM lesion remyelination, explained 68%–70% of the variance of clinical scores ( p < 0.01). Conclusion: Our multimodal and multicompartment approach allows us to explore single-patient cortical and WM lesion demyelination and remyelination, and to generate clinically relevant indices of myelin repair. These indices may be used as outcome measures in clinical trials, thus increasing the chance to identify successful promyelinating treatments in patients with MS.